2021
DOI: 10.1016/j.pragma.2021.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Responsibility attribution in gender-based domestic violence: A study bridging corpus-assisted discourse analysis and readers' perception

Abstract: This paper investigates how argument structure constructions (see e.g. Goldberg 1995) are used by Italian newspapers to portray gender-based violence (GBV), how their usage affects responsibility attribution to perpetrators, and how such usage is perceived by Italian readers. The assumption is that constructions critically affect meaning: constructional choices prompt different viewpoints of the same event. For the corpus study, we collected 40 articles from local newspapers and annotated 720 constructions den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
1
18
0
6
Order By: Relevance
“…For instance, Te Brömmelstroet (2020) shows that media in the Netherlands frequently report on traffic crashes by foregrounding the more vulnerable participants (e.g., pedestrians or cyclists), while backgrounding car drivers. A similar pattern has been observed for news reports of femicides in Italy, where the victim tends to be foregrounded and the perpetrator backgrounded Meluzzi et al, 2021).…”
Section: Semantic Frames For Events In Societysupporting
confidence: 78%
“…For instance, Te Brömmelstroet (2020) shows that media in the Netherlands frequently report on traffic crashes by foregrounding the more vulnerable participants (e.g., pedestrians or cyclists), while backgrounding car drivers. A similar pattern has been observed for news reports of femicides in Italy, where the victim tends to be foregrounded and the perpetrator backgrounded Meluzzi et al, 2021).…”
Section: Semantic Frames For Events In Societysupporting
confidence: 78%
“…Similarly, Meluzzi et al (2021) investigated the effect of grammatical structures on attributing responsibility to offenders. Participants read a media report about gender-based violence and responded to four speculative questions about the offender and the victim.…”
Section: Grammatical Structure Effectmentioning
confidence: 99%
“…It has been shown that the variability of linguistic expressions used to describe an event impacts the reader's perception of the event and its social significance. Previous work in psycholinguistics shows that in events involving violence (at any level), the linguistic backgrounding of agents hinders their responsibility and promote victim blaming (Huttenlocher et al, 1968;Bohner, 2001;Gray and Wegner, 2009;Zhou et al, 2021;Meluzzi et al, 2021). For instance, Te Brömmelstroet (2020) shows that media in the Netherlands frequently report on traffic crashes by foregrounding the more vulnerable participants (e.g., pedestrians or cyclists), while backgrounding car drivers.…”
Section: Semantic Frames For Events In Societymentioning
confidence: 99%